Environmental management systems as a driver for sustainability: state of implementation, benefits and barriers in German construction companies - Schmidt, Jan-Simon; Osebold, Rainard (Journal of Civil Engineering and Management, 2017)
The construction industry, as one of almost every economy’s major generators of environmental impact, can contribute in large measure to achieving the goals of sustainability. However, most publications in this field deal with sustainability with reference to selecting construction materials and improvements in the operating phase of buildings. When considering ecological sustainability the focus has to be extended from the finished building to the building process. Therefore the actors of the construction sector who are responsible for the production process have to be studied: the construction companies. The goal of this paper is to study the state of ecologically sustainable corporate business management in construction. The state of application of elements of environmental management systems (EMS) is used as an indicator of the current situation in German construction companies. EMS can help continuously to environmentally improve the operating processes of the firms. A broad survey about the extent of EMS has been conducted considering the barriers and drivers. In general, a relatively low interest in EMS and a lack of knowledge is noticeable within the sector. As a result, strategic recommendations are made on how to promote environmental management to foster sustainable thinking in the German construction industry.